Ações educativas em grupo para gestantes na atenção primária: revisão integrativa - Rosa, Elisângela Cristina (2019)
Introduction: Group educational actions with pregnant have the potential to reduce health risk in this period, both for the woman and for her baby, which justifies the importance of the work performed by health professionals in primary care. Objective: To analyze the groups in the context of carrying out educative actions for pregnant women in Primary Health Care. Method: This was a study carried out under the scope of bibliographical research, of a descriptive and qualitative nature, elaborated in an orderly way for the analysis and conclusion of the selected texts, in order to answer the research question, elaborated from the format PICOT. From the definition of the descriptors for the delimitation of the research, it was sought to find publications potentially appropriate for the study in question. From a total of 351 works, published in the databases Medline (66), Lilacs (43) and BDEnf (14), 15 publications were selected to include in the Integrative Review. The others (336) were excluded because they were studies that presented dissonance with the criteria used for inclusion. Result: The study observed that educational actions along with the group of pregnant are extremely important for both the mother and the baby. Since through dynamics, one can stimulate self-esteem and self-confidence, as well as reduce anxiety and expectations regarding the baby, both the pregnant and those close to her. Conclusion: It is concluded that the survey of the scientific articles provided a better understanding of the existing group interventions in primary health care and of the pediatric models used. In addition, it was possible to identify that further studies need to be performed in order to have a better knowledge about the group educational actions for pregnant women